Teachers' islamic religious education lesson planning in accommodating students with special needs at purworejo state special elementary school - Laelatul Fitriyah; Nur Rohmah Hayati (Yayasan Azhar Amanaa Yogyakarta, 2026)
Abstract:Lesson planning constitutes one of the fundamental aspects in determining the quality of Islamic Religious Education (IRE) services for students with special needs. Although numerous studies have examined the implementation of IRE instruction for students with special needs, research focusing specifically on the planning stage remains relatively limited, particularly within the context of Special Elementary Schools (Sekolah Dasar Luar Biasa [SDLB]). This study aimed to analyze how IRE teachers plan instruction to accommodate the learning needs of students with special needs, identify the forms of instructional accommodations employed, and examine the supporting and inhibiting factors influencing the instructional planning process at SDLB Negeri Purworejo. This study employed a qualitative approach using a case study design. The research was conducted at SDLB Negeri Purworejo, with Islamic Religious Education teachers serving as the research participants. Data were collected through interviews, observations, and document analysis and were subsequently analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing. The findings revealed that instructional planning began with identifying students’ prior abilities, learning needs, and individual characteristics. Instructional accommodations were implemented by adapting learning objectives, instructional materials, teaching methods, learning media, and assessment procedures to meet students’ individual needs. The diversity of students’ characteristics constituted the primary consideration in developing instructional plans, while teachers’ professional competence, teaching experience, and the availability of instructional media served as the main supporting factors. Conversely, limited expertise in special education, the heterogeneous abilities of students, and the high demand for individualized assistance emerged as the principal challenges. This study contributes to the growing body of knowledge on adaptive Islamic Religious Education lesson planning for students with special needs and provides practical insights for the development of differentiated instruction in special education settings.Abstrak:Perencanaan pembelajaran merupakan salah satu aspek fundamental dalam menentukan kualitas layanan Pendidikan Agama Islam (PAI) bagi siswa berkebutuhan khusus. Meskipun berbagai penelitian telah membahas pelaksanaan pembelajaran PAI pada siswa berkebutuhan khusus, kajian mengenai aspek perencanaan pembelajaran masih relatif terbatas, khususnya pada konteks Sekolah Dasar Luar Biasa (SDLB). Penelitian ini bertujuan untuk menganalisis perencanaan pembelajaran PAI yang dilakukan guru dalam mengakomodasi kebutuhan siswa berkebutuhan khusus, mengidentifikasi bentuk-bentuk akomodasi yang diterapkan, serta mengungkap faktor pendukung dan faktor penghambat yang memengaruhi proses perencanaan pembelajaran di SDLB Negeri Purworejo. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Penelitian dilakukan di SDLB Negeri Purworejo dengan subjek penelitian guru PAI. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perencanaan pembelajaran diawali dengan identifikasi kemampuan awal, kebutuhan belajar, dan karakteristik siswa berkebutuhan khusus. Akomodasi pembelajaran dilakukan melalui penyesuaian tujuan, materi, metode, media, dan evaluasi pembelajaran sesuai dengan kebutuhan peserta didik. Keberagaman karakteristik siswa menjadi pertimbangan utama dalam penyusunan perencanaan pembelajaran, sedangkan kompetensi guru, pengalaman mengajar, dan ketersediaan media pembelajaran menjadi faktor pendukung utama. Adapun keterbatasan kompetensi pendidikan khusus, heterogenitas kemampuan siswa, dan tingginya kebutuhan pendampingan individual menjadi faktor penghambat. Penelitian ini berkontribusi dalam memperkaya kajian tentang perencanaan pembelajaran PAI yang adaptif bagi siswa berkebutuhan khusus serta menjadi rujukan bagi pengembangan pembelajaran berdiferensiasi pada pendidikan khusus.